Persea pumila (Lauraceae), a New Species from the Brazilian Serra da Mantiqueira Mountain Range - Moraes, Pedro L. R. de [UNESP]; Pacheco, Renato S. [UNESP]; Meireles, Leonardo D. (Amer Soc Plant Taxonomists, 2014)
Persea pumila, a new species of Lauraceae from a Brazilian high-altitude grassland is described and illustrated. The new species belongs to Parses subg. Eriodaphne. It is distinguished from other neotropical Persea species by the shrubby habit in combination with obovate, glabrous, abaxially papillose leaves densely overlapping each other, glabrous inflorescences, and sparsely pubescent flowers. Its morphological distinctiveness and its relationships with probable allied species are discussed.
Keywords: Atlantic rain forest; Brazil; high-altitude grasslands; Persea subg. Eriodaphne; taxonomy